Tennis injuries: occurrence, aetiology, and prevention - Pluim, B. M.; Staal, J. B.; Windler, G. E.; Jayanthi, N. (British Journal of Sports Medicine, 2006)
A systematic search of published reports was carried out in three electronic databases from 1966 on to identify relevant articles relating to tennis injuries. There were 39 case reports, 49 laboratory studies, 28 descriptive epidemiological studies, and three analytical epidemiological studies. The principal findings of the review were: first, there is a great variation in the reported incidence of tennis injuries; second, most injuries occur in the lower extremities, followed by the upper extremities and then the trunk; third, there have been very few longitudinal cohort studies that investigated the association between risk factors and the occurrence of tennis injuries (odds ratios, risk ratios, hazard ratios); and fourth, there were no randomised controlled trials investigating injury prevention measures in tennis. More methodologically sound studies are needed for a better understanding of risk factors, in order to design useful strategies to prevent tennis injuries.